Pengaruh Model Kontekstual Teknik Teratai terhadap Kemampuan Menulis Puisi Siswa Kelas V SDN Kota Bengkulu - Nadia Safitri Nadia; Resnani; Neza Agusdianita (Universitas Bengkulu, 2023)
The purpose of this research is to know the Influence of Usage of Contextual Model of Lotus Technique to Writing Poetry Skill of Grade V of SDN at Gugus III of Bengkulu City. This type of research is quantitative research. The research method used is Quasi Experimental Design by using the design type The Matching Only Posttest Control Group Design. The population in this study is all students of State Elementary School students of class V in Gugus III of Bengkulu City. The sampling technique using Cluster Random Sampling and obtained V SDN 57 Kota Bengkulu as experiment class with the number of 24 students and class of SD SDN 17 Kota Bengkulu as control class amounted to 24 students. The research instrument used in the form of a test of writing poetry given through posttest (after the learning took place). The data of this research were analyzed using descriptive and inferential analysis (t-test). Data of this research are analyzed by using inferential analysis that is t-test (mann whitney u test). From result of research known by result of t-test with tcount equal to 6,20 and value table with significant level 5% 4,390. So with thitung (6.20)> ttable (4,390). The value of tcount obtained is bigger than ttable value hence can be concluded that there is influence of usage of contextual model of lotus technique to poetry writing skill of class V SDN student in Gugus III Kota Bengkulu.